EFFICACY OF AI +hCG AND POST-AI PROGESTERONE SUPPLEMENTATION FOR ENHANCING FERTILITY AND PLASMA PROGESTERONE AND BIOCHEMICAL PROFILE IN REPEAT BREEDING COWS AND BUFFALOES - Parmar, CP; Patel, DM; Dhami, AJ; Hadiya, KK; Panchal, MT; Patel, JA; Buhecha, KV; Killedar, A (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was conducted to evaluate the efficacy of i/m Inj.of hCG1500 IU along with mid-estrus AI or Inj. hydroxy-progesterone caproate 500 mg on day 5th post-AI in 20 each repeat breeding cows and buffaloes in terms of conception rate and plasma progesterone and biochemical profile in comparison to normal cyclic controls. The conception rates in repeat breeding cows and buffaloes during progesterone supplemented cycle were 40 and 30 %, respectively, whereas 30 % cows and buffaloes each conceived under AI+hCG protocol and 40 % each in control groups. The overall 3 cycles’ conception rates under AI+hCG groups were identical 60 %in both cows and buffaloes. The corresponding overall conception rates for cows and buffaloes under progesterone supplementation groups were 60 and 50 %, and in control groups 70 and 60 %, respectively. The mean plasma progesterone concentrations of cows and buffaloes on day of AI in all 3 groups were identical and basal. The values on day 21 post-AI in cows and buffaloes under AI+hCG protocol (4.23±1.87 and 2.89±1.18 ng/ml), progesterone supplementation (2.62±1.03 and 2.50±0.77 ng/ml) and normal cyclic (4.23±1.56 and 3.69±1.20 ng/ml) group also did not vary significantly, but the conceived animals had significantly higher plasma progesterone than non-conceived animals in all groups. The plasma total protein, cholesterol,calcium and phosphorusprofile neither varied significantly between days nor between conceived and non-conceived groups. In conclusion, both AI + hCG and post-AI progesterone injections, though did not influence the plasma progesterone or biochemical profile, effectively enhanced pregnancy rate in repeat breeding cows and buffaloes close to the normal cyclic control groups under field condition.
Keywords: Crossbred cows; Buffaloes; Repeat breeding; hCG therapy; Progesterone; supplementation; Conception rate; Plasma progesterone & biochemical profile